Maternal mortality by direct obstetric causes in an urban referral hospital: case of Boulmiougou District Hospital in Ouagadougou, Burkina Faso - Sawadogo, Yobi Alexis; Zamané, Hyacinthe; Kiemtoré, Sibraogo; Sib, Sansan Rodrigue; Kain, Dantola Paul; Ouédraogo, Issa; Ouattara, Adama; Ouédraogo, Charlemagne; Ouédraogo, Ali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Complications during pregnancy and childbirth are the leading causes of death and disability for women of childbearing age. Objective of this study was to study maternal mortality of direct obstetric origin at the Boulmiougou district hospital from 2010 to 2014. Methods: This was a retrospective cross-sectional descriptive and analytical study of maternal deaths by direct obstetric cause at the maternity ward of Boulmiougou District Hospital during the period from January 1st 2010 to December 31st, 2014, i.e. 5 years. Results: The maternal mortality rate by direct obstetric cause of 147.68 maternal deaths per 100,000 live births. The average age of the patients was 27.09 years old. The direct causes of maternal death were hemorrhage (47.06%), hypertensive disorders (20.59%), infections (14.71%) and unsafe abortion (11.76%). Contributing factors to maternal deaths were delay in evacuation (47.06%) and delay in care (38.23%). Conclusions: Maternal mortality remains high in the Boulmiougou District Hospital. To effectively combat maternal mortality, it is important to focus on the continuous training of staff and the strengthening of the technical platform.